Is It Possible to Expand Oocyte Donors by Decreasing Number of Oocytes for Own Use? Insights From a Large Single-Center Study - Zhiqin Bu (Frontiers Media S.A., 2021)
BackgroundCurrently, in China, only women undergoing in vitro fertilization/intracytoplasmic sperm injection (IVF/ICSI) cycles can donate oocytes to others, but at least 15 oocytes must be kept for their own treatment. Thus, the aim of this study was to determine whether oocyte donation compromises the cumulative live birth rate (CLBR) of donors and whether it is possible to expand oocyte donors’ crowd.MethodsThis was a retrospective cohort study from August 2015 to July 2017 including a total of 2,144 patients, in which 830 IVF–embryo transfer (IVF-ET) patients were eligible for oocyte donation and 1,314 patients met all other oocyte donation criteria but had fewer oocytes retrieved (10–17 oocytes). All 830 patients were advised to donate approximately three to five oocytes to others and were eventually divided into two groups: the oocyte donation group (those who donated) and the control group (those who declined). The basic patient parameters and CLBR, as well as the number of supernumerary embryos after achieving live birth, were compared. These two factors were also compared in all patients (2,144) with oocyte ≥10.ResultsIn 830 IVF-ET patients who were eligible for oocyte donation, only the oocyte number was significantly different between two groups, and the donation group had more than the control group (25.49 ± 5.76 vs. 22.88 ± 5.11, respectively; p = 0.09). No significant differences were found between the two groups in other factors. The results indicate that the live birth rate in the donation group was higher than that in the control group (81.31% vs. 82.95%, p = 0.371), without significance. In addition, CLBR can still reach as high as 73% when the oocyte number for own use was 10. Supernumerary embryos also increased as the oocyte number increased in all patients (oocyte ≥10).ConclusionsCurrently, oocyte donation did not compromise CLBR, and oocyte donation can decrease the waste of embryos. In addition, in patients with 10 oocytes retrieved, the CLBR was still good (73%). Thus, it is possible to expand oocyte donors if the number of oocyte kept for own use was decreased from 15 to 10 after enough communication with patients.